Sous vide cook-chill mussel (Mytilus galloprovincialis): evaluation of chemical, microbiological and sensory quality during chilled storage (3 °C). (May 2018) - Bongiorno, Tiziana; Tulli, Francesca; Comi, Giuseppe; Sensidoni, Alessandro; Andyanto, Debbie; Iacumin, Lucilla
Abstract: The changes in the chemical, physical, microbiological and sensory qualities of sous vide cooked processed mussels in comparison with conventional cooked mussels (90°C-10 min) were monitored during chilled storage (3.0 ± 1 °C). The sous vide cook and chill method at 85 °C for 10 min with or without salt brine resulted in being able to preserve the quality of mussels and extend their shelf-life to 21 storage days. Moreover, with the addition of brine a shelf-life extension of up to 30 days was possible, in comparison to mussels subjected to conventional cooking. The use of brine, other then facilitating packaging procedures preventing micro ruptures, showed a positive effect on moisture content (81.4 vs 73.5%), TVB-N (10.4 vs 16.7 mg N/100 g), reduced bacterial growth and sensory attributes, such as meat turgidity of mussels. Mussels processed by " sous vide cook and chill" method, marketed at refrigerated conditions, may be a promising addition to "ready to eat" and "ready to cook" food products with an extended shelf-life and high versatility as requested by the changes in consumer habits. Highlights: Use of sous vide processing (85 °C, 10 min) with/without salt brine on mussels. Microbiological quality of processed mussels preserved beyond 15 days. Mussels processed by sous vide extended shelf-life to 21 days. Brine extended shelf-life to 30 days for sous vide processed mussels. Sensory quality of processed mussels acceptable over 14 days.